Xiaoyaosan Exerts Therapeutic Effects on the Colon of Chronic Restraint Stress Model Rats via the Regulation of Immunoinflammatory Activation Induced by the TLR4/NLRP3 Inflammasome Signaling Pathway. (8th January 2021) - Zhu, Hui-Zheng; Liang, Yu-Dan; Hao, Wen-Zhi; Ma, Qing-Yu; Li, Xiao-Juan; Li, Yu-Ming; Chen, Jia-Xu
Abstract : Depression is the neurological manifestation most commonly associated with gastrointestinal diseases. The release of inflammatory cytokines mediated by TLR4/NLRP3 inflammasome signaling-induced immunoinflammatory activation may represent a common pathogenic process underlying the development of gastrointestinal diseases and depression. Clinical studies have indicated that Xiaoyaosan (XYS) can relieve depressive behavior by improving gastrointestinal symptoms. We previously demonstrated that XYS can reduce colonic inflammation in a rat model of chronic unpredictable mild stress; however, the precise anti-inflammatory mechanisms involved remain unclear. Here, we investigated whether XYS can ameliorate depressive behavior through regulating the TLR4/NLRP3 inflammasome signaling pathway, thereby inhibiting immunoinflammatory activation and reducing colonic proinflammatory cytokine levels. Fifty-two healthy male Sprague–Dawley rats were randomly divided into four groups (control, model, XYS, and fluoxetine). The latter three groups were subjected to 21 days of chronic restraint stress to generate a model of stress-induced depression. XYS and fluoxetine were administered intragastrically. Behavioral changes in the rats were assessed after 21 days. Serum and colon samples were collected, and the relative levels of the inflammation indicators IL-6, IL-1 β, and TNF- α were determined by ELISA. Pathological changes in colon tissue were assessed by hematoxylin and eosin staining. The levels of TLR4, MyD88, NF- κ B-p65, TAK1, IRAK1, and TRAF6 were detected by immunohistochemistry, while the gene and protein expression levels of TLR4, MyD88, NF- κ B-p65, TAK1, IRAK1, TRAF6, NLRP3, ASC, and caspase-1 were detected by quantitative polymerase chain reaction (qPCR) and Western blotting. The results indicated that XYS could improve the depressive-like behavior and the weight loss of rats with stress-induced depression. Furthermore, depressed rats treated with XYS exhibited decreased expression levels of TLR4, MyD88, NF- κ B-p65, TAK1, IRAK1, TRAF6, NLRP3, ASC, and caspase-1 in colonic tissue; reduced colon and serum concentrations of the inflammatory factors IL-6, IL-1 β, and TNF- α ; and lowered levels of colonic inflammation.